A Culture of Chain Mobility Among Small Islanders: A Case Study of Lease Islanders' Mobility to Ambon City - Murwani, Prapti (KnE Social Sciences, 2024)
People who live in the archipelago have a high mobility culture. The life of the people makes the island not a separator from the mainland, but the island is believed to be an inseparable part. Land and sea become one unit of life for people living on small islands. Therefore, mobility is also part of their lives, so the sea is not a barrier to their mobility. This research aims to explain the cultural process of chain mobility of Lease Islands residents to Ambon City. The research method used is the case study method because this research aims to reveal the behavior and cultural process of chain mobility of island communities. This research uses a single case study method. The number of case units in this study was 7 case units. The results showed that the migrant network in the destination area is one of the critical factors and is very influential in the migrant's decision to migrate or stay in origin. The network of previous migrants who have formed in the city is one of the factors that determine the continuity of migrants to stay in the destination area. This lengthy process of mobility creates intergenerational mobility. It is shown by the existence of clans from the Lease Islands found also in Ambon City. The clans have developed and come from generations whose sequence is no longer known, only known from the name of the clan that follows it. The facts on the field show that mobility is a way of life for islanders. Observations in origin also show that almost every family has family members who live outside the island, especially in Ambon City. Keywords: hain mobility, culture, small Island, lease